Structural development of the HIV-1 apex-directed PGT145-PGDM1400 antibody lineage - Rosemarie D. Mason; Baoshan Zhang; Nicholas C. Morano; Chen-Hsiang Shen; Krisha McKee; Ashley Heimann; Renguang Du; Alexandra F. Nazzari; Shelby Hodges; Tapan Kanai; Bob C. Lin; Mark K. Louder; et al. (Cell Reports)
Summary: Broadly neutralizing antibodies (bNAbs) targeting the apex of the HIV-1-envelope (Env) trimer comprise the most potent category of HIV-1 bNAbs and have emerged as promising therapeutics. Here, we investigate the development of the HIV-1 apex-directed PGT145-PGDM1400 antibody lineage and report cryo-EM structures at 3.4 Å resolution of PGDM1400 and of an improved PGT145 variant (PGT145-R100aS), each bound to the BG505 Env trimer. Cross-species-based engineering improves PGT145 IC80 breadth to near that of PGDM1400. Despite similar breadth and potency, the two antibodies differ in their residue-level interactions with important apex features, including N160 glycans and apex cavity, with residue 100i of PGT145 (sulfated tyrosine) penetrating ∼7 Å farther than residue 100i of PGDM1400 (aspartic acid). While apex-directed bNAbs from other donors use maturation pathways that often converge on analogous residue-level recognition, our results demonstrate that divergent residue-level recognition can occur within the same lineage, thereby enabling improved coverage of escape variants.